2016
DOI: 10.1099/jmm.0.000342
|View full text |Cite
|
Sign up to set email alerts
|

Whole-cell Proteus mirabilis urease inhibition by aminophosphinates for the control of struvite formation

Abstract: The study evaluated the in vitro impact of a series of aminophosphinic urease inhibitors on Proteusmirabilis. The group of compounds comprised structurally diverse analogues of diamidophosphate built on an N-C-P scaffold. The influence of urease inhibition on urea-splitting activity was assessed by whole-cell pH-static kinetic measurements. The potential to prevent struvite formation was determined by monitoring changes in pH and ionic composition of artificial urine medium during P. mirabilis growth. The most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The growing resistance of pathogenic strains to popular antibiotics encourages the search for novel antimicrobials [28]. Compounds of natural origin represent a promising group with antibacterial, antifungal, and antiviral activities [2,29].…”
Section: Resultsmentioning
confidence: 99%
“…The growing resistance of pathogenic strains to popular antibiotics encourages the search for novel antimicrobials [28]. Compounds of natural origin represent a promising group with antibacterial, antifungal, and antiviral activities [2,29].…”
Section: Resultsmentioning
confidence: 99%
“…Acetohydroxamate efficiency was weaker ( K i = 23.2 μM). Recently, we showed that the two compounds 4 and 13 exceeded the ability of acetohydroxamic acid to prevent struvite formation in an artificial Proteus mirabilis urine infection model [42]. Therefore, whole-cell H .…”
Section: Discussionmentioning
confidence: 99%
“…MIC 90 was not recorded within examined range of concentrations (50-250 μg/mL). [29] Still, it exhibited a slight antibacterial activity against all examined bacterial strains with the strongest bacteriostatic activity towards B. subtilis.…”
Section: Resultsmentioning
confidence: 93%